Proceedings of International Conference on Recent Trends in Computing ICRTC 2021 - Mahapatra, Rajendra Prasad; Peddoju, Sateesh Kumar; Roy, Sudip; Parwekar, Pritee; Goel, Lavika (Lecture Notes in Networks and Systems, 2022)
XXVII, 837 p. 399 illus., 308 illus. in color.